2015
DOI: 10.1039/c4cp05861e
|View full text |Cite
|
Sign up to set email alerts
|

Containerless solidification of undercooled SrO–Al2O3 binary melts

Abstract: The solidification of the SrO-Al2O3 binary system was investigated under containerless conditions using an aerodynamic levitation furnace. Glass formation was observed in compositions with 35-45 mol% SrO and 55-75 mol% SrO. Cooling curves were obtained at a constant cooling rate in the range of 1-1000 °C s(-1). The crystallization temperature was apparently independent of the cooling rate and far below the melting point when the sample was fully crystallized, whereas it decreased when the sample was partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Second, all the yAl 2 O 3 •xSrO• (100‐ y ‐ x ) CaO glasses can be easily prepared utilizing the laser‐heated aerodynamic levitation furnace (ALF) built at Wuhan University of Technology. For the glass‐forming regions through the similar equipment in the Al 2 O 3 ‐SrO and Al 2 O 3 ‐CaO systems, see the recent report . Therefore, a series of aluminate glasses with the compositions (mol%): 58Al 2 O 3 •xSrO• (42‐ x ) CaO ( x = 0, 10.5, 21, 31.5, 42 molar percent), were prepared by melting a batch of Al 2 O 3 , CaO and SrO powder with the purity of 99.99%.…”
Section: Methodsmentioning
confidence: 99%
“…Second, all the yAl 2 O 3 •xSrO• (100‐ y ‐ x ) CaO glasses can be easily prepared utilizing the laser‐heated aerodynamic levitation furnace (ALF) built at Wuhan University of Technology. For the glass‐forming regions through the similar equipment in the Al 2 O 3 ‐SrO and Al 2 O 3 ‐CaO systems, see the recent report . Therefore, a series of aluminate glasses with the compositions (mol%): 58Al 2 O 3 •xSrO• (42‐ x ) CaO ( x = 0, 10.5, 21, 31.5, 42 molar percent), were prepared by melting a batch of Al 2 O 3 , CaO and SrO powder with the purity of 99.99%.…”
Section: Methodsmentioning
confidence: 99%
“…However, TiO 2 ‐based glasses without any conventional network‐former can only be prepared by containerless processing due to their poor glass‐forming abilities 6−8 . To date, TiO 2 ‐based, Nb 2 O 5 ‐based, 9−11 Al 2 O 3 ‐based, 12−14 and Ga 2 O 3 ‐based 15−17 glasses have been vitrified by containerless processing technique. Arai et al 18 synthesized a La 4 Ti 9 O 24 glass, which exhibited a high refractive index of 2.231 at 1313 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Al 2 O 3 ‐based glasses are generally difficult to fabricate in bulk because of their low glass‐forming ability. A levitation technique that promotes deeper undercooling and avoids crystallization of the melt allows the production of bulk glasses with a small size, for example, A O–Al 2 O 3 ( A = alkaline‐earth elements), Al 2 O 3 –SiO 2 , R 2 O 3 –Al 2 O 3 ( R = are earth elements), and Ta 2 O 5 –Al 2 O 3 . It has already been reported that Al 2 O 3 –SiO 2 and Ta 2 O 5 –Al 2 O 3 glasses have fascinating mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…(R = are earth elements), and Ta 2 O 5 -Al 2 O 3 . 11,22,[24][25][26] It has already been reported that Al 2 O 3 -SiO 2 and Ta 2 O 5 -Al 2 O 3 glasses have fascinating mechanical properties. In this paper, we report the elastic properties and crack initiation in a variety of rare-earth aluminate glasses.…”
Section: Introductionmentioning
confidence: 99%